2012
DOI: 10.2319/060811-375.1
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric evaluation of children with familial Mediterranean fever

Abstract: The hypothesis is rejected. Significant differences exist between the craniofacial morphology of patients with FMF and the healthy population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
7
0
2
Order By: Relevance
“…The cephalograms were taken in a natural head position with the teeth in centric occlusion. 15,16 A line passing through tuberculum sellae (intersection of the mandibular contours of the anterior clinoid processes and the anterior wall of the sella) and wing point (intersection of the contour of ala major with the jugum sphenoidale) was used as the horizontal reference line (HRL) and a perpendicular line passing through tuberculum sellae as the vertical reference line (VRL) ( Figure 4). Twenty-seven angular and linear measurements were performed on the cephalograms (Figures 5 and 6) and [ Table 1].…”
Section: Methodsmentioning
confidence: 99%
“…The cephalograms were taken in a natural head position with the teeth in centric occlusion. 15,16 A line passing through tuberculum sellae (intersection of the mandibular contours of the anterior clinoid processes and the anterior wall of the sella) and wing point (intersection of the contour of ala major with the jugum sphenoidale) was used as the horizontal reference line (HRL) and a perpendicular line passing through tuberculum sellae as the vertical reference line (VRL) ( Figure 4). Twenty-seven angular and linear measurements were performed on the cephalograms (Figures 5 and 6) and [ Table 1].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, it was found that the inflammation and the arthritis in FMF may affect the bone turnover of the condyle. 26 Studies showed that continuous inflammation decreases the bone mineral density causing altered body composition and growth impairment. 27 The inflammatory process in FMF may cause retarded mandibular or maxillary growth, respectively 26 and decreased mandibular bone density.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, subjects with skeletal malocclusions including crossbite and sagittal malocclusions, systemic diseases affecting the growth and development of the teeth and tooth agenesis excluding third molars were excluded because these could affect growth and development. [ 9 10 11 12 13 14 ]…”
Section: Discussionmentioning
confidence: 99%